The diel feeding rhythm of the freshwater crab Trichodactylus borellianus (Decapoda: Brachyura) in mesocosm and natural conditions - Azevedo Carvalho, Débora (2013)
Biorhythm studies have rarely used feeding rhythms of freshwater crustaceans to assess the internal clock. Even less often, they have compared the diel rhythms of juveniles and adults. In this study, the 24-h cyclic feeding behavior of the freshwater crab Trichodactylus borellianus was investigated in mesocosm and natural field conditions during summer. Sampling occurred throughout the day and included the dawn and dusk periods. The fullness of the stomach was used to characterize the feeding cycle and was analyzed with MESOR and a three-day time series plot. The rhythms of juveniles and adults were analyzed in the field. A bimodal feeding rhythm with midday and midnight peaks was observed in adults in the field, while juveniles had an asynchronous behavior. Mesocosm animals also showed no cyclic behavior. Rhythmic responses to nonphotic cues may result from a trade-off between foraging at an optimum time and shifting the diel rhythm to avoid competition and predation risk. Juvenile feeding asynchrony could be a strategy that allows them to be active in the same habitat as adults.